Analysis of Musytarak Al-Lafdzi the Word “Kutiba” in the Qur'an: A Study of Semantic Analysis - Hima Roiku Dinia; Unzilatun Nikmah; Nur Ila Ifawati (Islamic Religious Education Departement, 2024)
The diversity of meanings in Musytarak lands in the Al-Qur'an is a challenge in the translation process, which causes ambiguity and the potential for multiple understandings if it needs to be translated or understood correctly. An example is lafadz,